Right parahippocampal volume deficit in an older population with posttraumatic stress disorder. (May 2021) - Basavaraju, Rakshathi; France, Jeanelle; Maas, Benjamin; Brickman, Adam M.; Flory, Janine D.; Szeszko, Philip R.; Yehuda, Rachel; Neria, Yuval; Rutherford, Bret R.; Provenzano, Frank A.
Abstract: Background: Posttraumatic Stress Disorder (PTSD) is an increasingly prevalent condition among older adults and may escalate further as the general population including veterans from recent conflicts grow older. Despite growing evidence of higher medical comorbidity, cognitive impairment and dementia, and disability in older individuals with PTSD, there are very few studies examining brain cortical structure in this population. Hence, we examined cortical volumes in a cross-sectional study of veterans and civilians aged ≥50 years, of both sexes and exposed to trauma (interpersonal, combat, non-interpersonal). Methods: Cortical volumes were obtained from T1-weighted structural MRI and compared between individuals with PTSD and Trauma Exposed Healthy Controls (TEHC) adjusting for age, sex, estimated intracranial volume, depression severity, and time elapsed since trauma exposure. Results: The PTSD group (N = 55) had smaller right parahippocampal gyrus compared to TEHC (N = 36), corrected p(pFWER ) = 0.034, with an effect size of 0.75 (Cohen's d), with no significant group differences in other cortical areas. Conclusions: These findings are different from the structural brain findings reported in studies in younger age groups (larger parahippocampal volume in PTSD patients), suggesting a possible significant change in brain structure as PTSD patients age. These results need replication in longitudinal studies across the age-span to test whether they are neuroanatomical markers representing disease vulnerability, trauma resilience or pathological neurodegeneration associated with cognitive impairment and dementia. Highlights: Cortical volumes were compared between PTSD and TEHC in a population >50 years. Right parahippocampal gyrus was smaller in PTSD compared to TEHC (pFWER  = 0.034). Depression severity was inversely correlated with bilateral frontal volumes. These findings are different from those reported in studies of younger age groups.